Електронне ліцензування освітньої діяльності у сфері вищої освіти: переваги та недоліки - Гелеш, Анна (Видавництво Львівської політехніки, 2018)
The author describes the system of electronic licensing of educational activities in the field of higher education. The advantages and disadvantages of such a procedure for educational institutions of Ukraine are highlighted.
Keywords: електронне ліцензування; освітня діяльність; ліцензійні умови; вища освіта